Acid-activated all-solid waste lightweight unburned ceramsite and preparation method and application thereof

Through the preparation method of acid-activated all solid waste light-fired pottery, acidic solid waste and other materials, the problems of high process complexity and cost in traditional processes are solved, and the efficient utilization of acidic solid waste and high-strength pottery is achieved. Preparation, suitable for lightweight buildings and sewage treatment.

CN118754476BActive Publication Date: 2025-02-18CCCC HIGHWAY BRIDGES NATIONAL ENGINEERING RESEARCH CENTRE CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411002705.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-25
Publication Date
2025-02-18
Estimated Expiration
2044-07-25

AI Technical Summary

Technical Problem

The prior art is difficult to utilize acidic solid waste - phosphogypsum and electrolytic manganese slag on a large scale, and the traditional fire-free ceramic granules process is cumbersome, high cost, and has a high environmental pollution.

Method used

The preparation method of acid-activated all solid waste light-fired pottery is adopted. By acid-induced phosphogypsum and electrolytic manganese slag, mixed with dolomite, fly ash, blast furnace slag and other materials, sprayed in and diluted by a high-pressure spray can The phosphoric acid solution is then cured after forming spherical particles to prepare lightweight calendering.

Benefits of technology

It realizes efficient utilization of acidic solid waste, reduces process complexity and cost, and the prepared fire-free ceramic granules have high strength and good heavy metal adsorption capabilities, and are suitable for lightweight building materials and sewage treatment industries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118754476B_ABST
    Figure CN118754476B_ABST
Patent Text Reader

Abstract

The present invention provides an acid-activated all-solid waste lightweight unburned ceramsite and a preparation method and application thereof, and relates to the field of lightweight building materials. The preparation method comprises: weighing the following raw materials by weight: 21-35 parts of phosphogypsum, 12-18 parts of electrolytic manganese slag, 14-20 parts of dolomite, 15-32 parts of fly ash, 10-18 parts of blast furnace slag, 10-15 parts of high-concentration phosphoric acid solution and 20-30 parts of water; acid-leaching the phosphogypsum, and then mixing and grinding with electrolytic manganese slag, dolomite, fly ash and blast furnace slag to obtain a mixed powder of unburned ceramsite raw materials; moving the mixed powder of unburned ceramsite raw materials to a granulator for stirring to obtain an unburned ceramsite mixture; diluting the high-concentration phosphoric acid solution, and spraying the diluted phosphoric acid solution into the granulator at a uniform speed through a high-pressure spray pot to prepare spherical particles; moving the spherical particles to a standard curing box for curing to obtain lightweight unburned ceramsite. The present invention utilizes phosphoric acid for excitation and foaming, has a simple process, low production energy consumption, and strong heavy metal solidification ability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention discloses the technical field of lightweight building materials, and more specifically relates to an acid-activated all-solid waste lightweight unburned ceramsite, and a preparation method and application thereof. Background Art

[0002] Expanded clay is an artificial lightweight aggregate made from shale, clay and industrial solid waste through firing and cooling. It has the advantages of thermal insulation and light weight, but traditional sintered expanded clay consumes huge amounts of energy and has high carbon emissions.

[0003] Phosphogypsum is a byproduct of the wet process of phosphoric acid production in industry, with a pH value of about 1.9-5.3. Electrolytic manganese slag is an acidic waste residue produced in the process of electrolyzing manganese sulfate solution to produce metallic manganese, with a pH value of about 5.9-6.6. Long-term open-air storage will lead to the fluoride, free phosphoric acid, high concentration of Mn and heavy metal ions (Cd 2+ Cr 3+ , Pb 2+ The use of phosphoric acid to stimulate phosphogypsum and electrolytic manganese slag to prepare unfired ceramsite can save process and increase the scale of utilization.

[0004] A low-carbon, environmentally friendly, unfired ceramsite filter material with application number CN202111424539.6, as well as a preparation method and use thereof, comprises: diluting a high-purity acid with water and mixing it with cement, fly ash, mineral powder, zeolite powder and kaolin to form an acid-activated material, then adding water, siliceous powder and expanded perlite to the acid-activated material, mixing and stirring the mixture evenly to form a matrix, and then undergoing foaming and pore formation, extrusion molding, normal pressure steam curing and high pressure steam curing, and surface modification to form a final ceramsite filter material product.

[0005] A variety of solid waste unfired ceramsite based on phosphogypsum and its preparation method with application number CN202210888343.0 are mainly composed of phosphogypsum, fly ash, phosphate tailings, cement, and admixtures. The raw materials are mixed evenly, then water is added for granulation, and finally aged and cured to obtain unfired ceramsite.

[0006] In the above-mentioned existing patent applications for unfired expanded clay, cement is used as the raw material, and the process is relatively complicated. At the same time, a high-temperature firing process is adopted for phosphogypsum and phosphate tailings. After high-temperature calcination, CaCO3 and MgCO3 in the raw materials are converted into CaO and MgO, which can be used as alkaline activating materials to activate the activity of fly ash. This effect cannot be achieved without calcination. However, calcination increases the processing cost and energy consumption. Therefore, it is necessary to propose a solution that is convenient to process and low in cost. Summary of the invention

[0007] In view of this, the present disclosure provides an acid-activated all-solid waste lightweight unfired ceramsite and a preparation method and application thereof, so as to solve the problem that it is difficult to utilize acidic solid waste - phosphogypsum and electrolytic manganese slag on a large scale, and make full use of the characteristics of raw materials and admixtures to improve the performance of unfired ceramsite.

[0008] According to one aspect of the present disclosure, a method for preparing acid-activated all-solid waste lightweight unburned ceramsite is provided, comprising:

[0009] S1: weigh the following raw materials in parts by weight: 21-35 parts of phosphogypsum, 12-18 parts of electrolytic manganese slag, 14-20 parts of dolomite, 15-32 parts of fly ash, 10-18 parts of blast furnace slag, 10-15 parts of high concentration phosphoric acid solution and 20-30 parts of water;

[0010] S2: acid-leaching the phosphogypsum, and then mixing and grinding it with electrolytic manganese slag, dolomite, fly ash and blast furnace slag to obtain a mixed powder of unburned ceramsite raw materials;

[0011] S3: moving the mixed powder of the unfired ceramsite raw materials to a granulator for stirring to obtain an unfired ceramsite mixture;

[0012] S4: diluting the high-concentration phosphoric acid solution, and spraying the diluted phosphoric acid solution into a granulator at a uniform speed through a high-pressure spray pot to prepare spherical particles;

[0013] S5: Move the spherical particles to a standard curing box for curing to obtain lightweight, unfired expanded clay.

[0014] According to an embodiment of the present disclosure, the phosphogypsum described in step S1 has a pH value less than or equal to 4.5 and a fineness greater than or equal to 0.25 mm.

[0015] According to an embodiment of the present disclosure, the acid leaching treatment of phosphogypsum described in step S2 includes: mixing oxalic acid and acetic acid solutions with a mass fraction of 1% each in a mass ratio of 1:2 to obtain an acidic solution, immersing the phosphogypsum in the acidic solution for immersion treatment, the immersion environment temperature is 25±2°C, the immersion time is 24 hours, and then drying in an oven at 50±5°C, sealing and standby. The purpose of the acid leaching treatment is to react the mixed solution of oxalic acid and acetic acid with the water-insoluble or slightly soluble calcium phosphate, calcium hydrogen phosphate, and calcium dihydrogen phosphate in the phosphogypsum to generate a substance that is easily soluble in water. The leached phosphate ions will promote the progress of the geopolymerization reaction, generate structural units such as PO-Si and PO-Al, and promote the formation of a gel matrix.

[0016] According to an embodiment of the present disclosure, the electrolytic manganese slag described in step S1 has a pH value less than or equal to 5.5 and a calcium sulfate dihydrate content greater than or equal to 40%. The addition of the above-mentioned phosphogypsum and electrolytic manganese slag can provide H +, reacts with the carbonate in the dolomite to generate CO2 gas, which creates pores inside the expanded clay and reduces the density.

[0017] According to an embodiment of the present disclosure, the dolomite described in step S1 has a magnesium calcium carbonate content greater than or equal to 60%. Dolomite can play a foaming role and promote the phosphate-based polymerization reaction. The addition of dolomite can release a large amount of CO2 gas in an acidic environment, making the unfired ceramsite lighter. The MgO in dolomite can solve the problems of instability and low early strength of the phosphoric acid excitation system. After adding dolomite, the rapid transformation of gel substances during the hydration reaction can be accelerated, thereby improving the workability and early strength of the phosphoric acid geopolymer. The improvement of early strength can improve the stability of foaming inside the matrix.

[0018] According to an embodiment of the present disclosure, the fly ash described in step S1 is grade II fly ash.

[0019] According to an embodiment of the present disclosure, the blast furnace slag in step S1 is of grade S95.

[0020] The addition of the fly ash and blast furnace slag can provide sufficient active silicon and aluminum raw materials for the acid-activated hydration process and promote the formation of gel.

[0021] According to the embodiment of the present disclosure, the high concentration phosphoric acid solution described in step S1 has a concentration of 8-10 mol / L. The addition of phosphoric acid at the above concentration can provide a strong acidic environment, PO tetrahedron and free PO4 3- The Si-Al precursor in the raw material can be dealuminated and dissolved under the action of acid etching. The dealuminated Si-O units react with PO tetrahedrons to form Si-OPO chains, gradually forming an amorphous gel. At the same time, the dissolved Al 3+ With free PO4 3- AlPO4 crystals are formed, and finally the two hydration products fill and bond with each other to form phosphoric acid geopolymers, which provide strength for the ceramsite matrix.

[0022] According to an embodiment of the present disclosure, the stirring in step S3 is carried out at a rotation speed of 65-75 r / min and lasts for 5-10 min.

[0023] According to an embodiment of the present disclosure, the dilution of the high concentration phosphoric acid solution in step S4 is performed according to a mass ratio of the high concentration phosphoric acid solution to water of (1-1.5):(3-4).

[0024] According to an embodiment of the present disclosure, the curing described in step S5 is to move the spherical particles into a standard curing box for curing for 28 days.

[0025] According to another aspect of the present disclosure, there is provided an acid-activated all-solid waste lightweight unburned ceramsite prepared by the method described.

[0026] According to another aspect of the present disclosure, there is provided an acid-activated all-solid waste lightweight unburned ceramsite prepared by the method, and its application in the fields of water treatment, construction or transportation.

[0027] The acid-activated all-solid waste lightweight unburned ceramsite and its preparation method and application provided by the present disclosure have the following beneficial effects compared with the prior art:

[0028] (1) The present invention proposes an acid-activated solution based on the characteristics of two acidic solid wastes, which eliminates the processes of pre-firing and neutralization treatment in traditional solutions, improves the convenience of treatment and reduces the treatment cost; and utilizes the natural acidic environment of phosphogypsum and electrolytic manganese slag to make them self-foaming to meet the density requirements of lightweight expanded clay, and prepares all-solid waste lightweight and high-strength expanded clay through the synergistic effect of multiple solid wastes.

[0029] (2) The present invention uses a composite acid solution to carry out acid leaching treatment on phosphogypsum. Oxalic acid and acetic acid react with calcium phosphate, calcium hydrogen phosphate and calcium dihydrogen phosphate that are insoluble or slightly soluble in water in the phosphogypsum to generate substances that are easily soluble in water. The leached phosphate ions promote the progress of geopolymerization reaction, generate structural units such as PO-Si and PO-Al, and promote the formation of a gel matrix.

[0030] (3) The present invention uses dolomite to improve the performance of all-solid waste expanded clay. Dolomite is rich in carbonates and MgO. The carbonates in the dolomite are used to foam in an acidic environment to reduce the density of the expanded clay. The synergistic optimization effect of phosphoric acid and magnesium oxide is used to promote the generation of Si-OPO, PO-Al and AlPO4, which can quickly form phosphoric acid geopolymer gelling materials at an early stage, thereby increasing the 28d strength by 40% to 55%.

[0031] (4) The phosphoric acid geopolymer-based unburned ceramsite prepared by the present disclosure has an excellent solidification effect on toxic substances in phosphogypsum and electrolytic manganese slag, especially heavy metal ions. In addition, the prepared unburned ceramsite can also purify the environment. The porous structure of the unburned ceramsite can adsorb small particles in the environment, and the phosphoric acid geopolymer gel can seal heavy metal ions through an ion exchange mechanism. Therefore, the prepared unburned ceramsite can be used in the sewage treatment industry in addition to preparing lightweight aggregate concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The above contents and other objects, features and advantages of the present disclosure will become more apparent through the following description of the embodiments of the present disclosure with reference to the accompanying drawings, in which:

[0033] Figure 1 A flow chart of a method for preparing acid-activated all-solid waste lightweight unburned ceramsite according to an embodiment of the present disclosure is shown. DETAILED DESCRIPTION

[0034] Hereinafter, embodiments of the present disclosure will be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present disclosure. In the following detailed description, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of the embodiments of the present disclosure. However, it is apparent that one or more embodiments may also be implemented without these specific details. In addition, in the following description, descriptions of known structures and technologies are omitted to avoid unnecessary confusion of the concepts of the present disclosure.

[0035] The terms used herein are only for describing specific embodiments and are not intended to limit the present disclosure. The terms "comprise", "include", etc. used herein indicate the existence of the features, steps, operations and / or components, but do not exclude the existence or addition of one or more other features, steps, operations or components.

[0036] All terms (including technical and scientific terms) used herein have the meanings commonly understood by those skilled in the art unless otherwise defined. It should be noted that the terms used herein should be interpreted as having a meaning consistent with the context of this specification and should not be interpreted in an idealized or overly rigid manner.

[0037] In order to solve the problem of difficulty in large-scale utilization of acidic solid waste - phosphogypsum and electrolytic manganese slag, and to make full use of the characteristics of raw materials and admixtures to improve the performance of unburned ceramsite, such as Figure 1 As shown, the present disclosure provides a method for preparing acid-activated all-solid waste lightweight unburned ceramsite, the method comprising the following steps:

[0038] S1: weigh the following raw materials in parts by weight: 21-35 parts of phosphogypsum, 12-18 parts of electrolytic manganese slag, 14-20 parts of dolomite, 15-32 parts of fly ash, 10-18 parts of blast furnace slag, 10-15 parts of high concentration phosphoric acid solution and 20-30 parts of water;

[0039] In this step, the pH value of the phosphogypsum is less than or equal to 4.5, and the fineness is greater than or equal to 0.25 mm. The pH value of the electrolytic manganese slag is less than or equal to 5.5, and the content of calcium sulfate dihydrate is greater than or equal to 40%. The addition of the phosphogypsum and electrolytic manganese slag can provide H + , reacts with the carbonate in the dolomite to generate CO2 gas, which creates pores inside the expanded clay and reduces the density.

[0040] The dolomite has a magnesium carbonate calcium content greater than or equal to 60%. Dolomite can play a foaming role and promote the phosphate-based polymerization reaction; the addition of dolomite can release a large amount of CO2 gas in an acidic environment, making the unburned ceramsite lighter. The MgO in dolomite can solve the problems of instability and low early strength of the phosphoric acid excitation system. After adding dolomite, the rapid transformation of gel substances in the hydration reaction process can be accelerated, thereby improving the workability and early strength of the phosphoric acid geopolymer. The improvement of early strength can improve the stability of foaming inside the matrix. Therefore, the present disclosure uses dolomite to improve the performance of all-solid waste ceramsite. Dolomite is rich in a large amount of carbonate and MgO. The carbonate in dolomite is used to foam in an acidic environment to reduce the density of ceramsite; the synergistic optimization effect of phosphoric acid-magnesium oxide is used to promote the generation of Si-OPO, PO-Al and AlPO4, and the phosphoric acid geopolymer gelling material can be quickly formed in the early stage, so that the 28d strength is increased by 40%~55%.

[0041] The fly ash is Grade II fly ash; the blast furnace slag is Grade S95; the addition of the fly ash and blast furnace slag can provide sufficient active silicon-aluminum raw materials for the acid-activated hydration process and promote the formation of gel.

[0042] The concentration of the high concentration phosphoric acid solution is 8-10 mol / L. The addition of phosphoric acid at the above concentration can provide a strong acidic environment, PO tetrahedron and free PO4 3- The Si-Al precursor in the raw material can be dealuminated and dissolved under the action of acid etching. The dealuminated Si-O units react with PO tetrahedrons to form Si-OPO chains, gradually forming an amorphous gel. At the same time, the dissolved Al 3+ With free PO4 3- AlPO4 crystals are formed, and finally the two hydration products fill and bond with each other to form phosphoric acid geopolymers, which provide strength for the ceramsite matrix.

[0043] Optionally, in this step, the raw materials are weighed in parts by weight as follows: 25-30 parts of phosphogypsum, 12-15 parts of electrolytic manganese slag, 16-20 parts of dolomite, 20-25 parts of fly ash, 15-18 parts of blast furnace slag, 13-15 parts of high-concentration phosphoric acid and 20-25 parts of water.

[0044] S2: acid-leaching the phosphogypsum, and then mixing and grinding it with electrolytic manganese slag, dolomite, fly ash and blast furnace slag to obtain a mixed powder of unburned ceramsite raw materials;

[0045] In this step, the acid leaching treatment of the phosphogypsum includes: mixing oxalic acid and acetic acid solutions with a mass fraction of 1% and a mass ratio of 1:2 to obtain an acid solution, immersing the phosphogypsum in the acid solution for immersion treatment, the immersion environment temperature is 25±2°C, the immersion time is 24 hours, and then drying in an oven at 50±5°C, sealing and standby. The purpose of the acid leaching treatment is to react the mixed solution of oxalic acid and acetic acid with the water-insoluble or slightly soluble calcium phosphate, calcium hydrogen phosphate, and calcium dihydrogen phosphate in the phosphogypsum to generate a substance that is easily soluble in water. The leached phosphate ions will promote the progress of the geopolymerization reaction, generate structural units such as PO-Si and PO-Al, and promote the formation of the gel matrix.

[0046] S3: moving the mixed powder of the unfired ceramsite raw materials to a granulator for stirring to obtain an unfired ceramsite mixture;

[0047] In this step, the stirring is carried out at a speed of 65-75 r / min for 5-10 min.

[0048] S4: diluting the high-concentration phosphoric acid solution, and spraying the diluted phosphoric acid solution into a granulator at a uniform speed through a high-pressure spray pot to prepare spherical particles;

[0049] In this step, the high concentration phosphoric acid solution is diluted according to the mass ratio of the high concentration phosphoric acid solution to water: (1-1.5): (3-4).

[0050] S5: Move the spherical particles to a standard curing box for curing to obtain lightweight unfired ceramsite;

[0051] In this step, the curing is to move the spherical particles into a standard curing box and cure them for 28 days.

[0052] Based on the above Figure 1 The method for preparing acid-activated all-solid waste lightweight unburned ceramsite shown is described in detail below in combination with Examples 1-5 and Comparative Example 1, and the method for preparing acid-activated all-solid waste lightweight unburned ceramsite provided by the present disclosure is described in detail.

[0053] Embodiment 1:

[0054] The present embodiment includes the following components in parts by weight: 25 parts of phosphogypsum (immersed in composite acid solution for 24 hours), 12 parts of electrolytic manganese slag, 12 parts of dolomite, 24 parts of II fly ash, 14 parts of S95 grade blast furnace slag, 13 parts of phosphoric acid, and water accounts for 35% of the mixture.

[0055] The above raw materials are mixed and added in order, granulated by a round pot granulator, and cured in a standard curing box for 28 days to obtain unfired ceramsite, which is then tested.

[0056] Embodiment 2:

[0057] The present embodiment includes the following components in parts by weight: 25 parts of phosphogypsum (immersed in composite acid solution for 24 hours), 12 parts of electrolytic manganese slag, 16 parts of dolomite, 20 parts of II fly ash, 14 parts of S95 grade blast furnace slag, 13 parts of phosphoric acid, and water accounts for 35% of the mixture.

[0058] The above raw materials are mixed and added in order, granulated by a round pot granulator, and cured in a standard curing box for 28 days to obtain unfired ceramsite, which is then tested.

[0059] Embodiment 3:

[0060] The present embodiment includes the following components in parts by weight: 25 parts of phosphogypsum (immersed in composite acid solution for 24 hours), 12 parts of electrolytic manganese slag, 20 parts of dolomite, 16 parts of II fly ash, 14 parts of S95 grade blast furnace slag, 13 parts of phosphoric acid, and water accounts for 35% of the mixture.

[0061] The above raw materials are mixed and added in order, granulated by a round pot granulator, and cured in a standard curing box for 28 days to obtain unfired ceramsite, which is then tested.

[0062] Embodiment 4:

[0063] The present embodiment includes the following components in parts by weight: 23 parts of phosphogypsum (immersed in composite acid solution for 24 hours), 12 parts of electrolytic manganese slag, 20 parts of dolomite, 16 parts of II fly ash, 14 parts of S95 grade blast furnace slag, 15 parts of phosphoric acid, and water accounts for 35% of the mixture.

[0064] The above raw materials are mixed and added in order, granulated by a round pot granulator, and cured in a standard curing box for 28 days to obtain unfired ceramsite, which is then tested.

[0065] Embodiment 5:

[0066] The present embodiment includes the following components in parts by weight: 21 parts of phosphogypsum (immersed in composite acid solution for 24 hours), 12 parts of electrolytic manganese slag, 20 parts of dolomite, 16 parts of II fly ash, 14 parts of S95 grade blast furnace slag, 17 parts of phosphoric acid, and water accounts for 35% of the mixture.

[0067] The above raw materials are mixed and added in order, granulated by a round pot granulator, and cured in a standard curing box for 28 days to obtain unfired ceramsite, which is then tested.

[0068] Comparative Example 1:

[0069] This comparative example includes the following components in parts by weight: 55 parts of fly ash, 25 parts of lime, 10 parts of cement, and 35% of water in the mixture.

[0070] The above raw materials are mixed and added in order, granulated by a round pot granulator, and cured in a standard curing box for 28 days to obtain unfired ceramsite, which is then tested.

[0071]

[0072] The unfired ceramsite prepared in the embodiment of the present disclosure meets the performance standard of GB / T 17431.1-2010 lightweight aggregate, and the 28d heavy metal ion dissolution content of Examples 1 to 5 is low, indicating that the unfired ceramsite prepared in the present disclosure has strong heavy metal adsorption and solidification capabilities, and can be used in sewage treatment materials or lightweight building materials.

[0073] It can be seen that the method for preparing acid-activated all-solid waste lightweight unfired ceramsite provided by the present invention proposes an acid-activated solution based on the characteristics of two acidic solid wastes, which eliminates the processes of pre-firing and neutralization treatment in traditional solutions, improves the convenience of treatment, and reduces the treatment cost; and utilizes the natural acidic environment of phosphogypsum and electrolytic manganese slag to make them self-foaming to meet the density requirements of lightweight ceramsite, and prepares all-solid waste lightweight and high-strength ceramsite through the synergistic effect of multiple solid wastes.

[0074] Further, based on the above-mentioned method for preparing acid-activated all-solid waste lightweight unburned ceramsite, the present disclosure also provides an acid-activated all-solid waste lightweight unburned ceramsite prepared by the method, and the acid-activated all-solid waste lightweight unburned ceramsite has an excellent solidification effect on toxic substances in phosphogypsum and electrolytic manganese slag, especially heavy metal ions. In addition, the acid-activated all-solid waste lightweight unburned ceramsite can also play a role in purifying the environment. The porous structure of the unburned ceramsite can adsorb small particles in the environment, and the phosphoric acid geopolymer gel can seal heavy metal ions through an ion exchange mechanism. Therefore, the prepared unburned ceramsite can be used in the sewage treatment industry in addition to preparing lightweight aggregate concrete.

[0075] Furthermore, based on the above-mentioned acid-activated all-solid waste lightweight unfired ceramsite and its preparation method, the present disclosure also provides an acid-activated all-solid waste lightweight unfired ceramsite prepared by the method, which can be widely used in water treatment, construction or transportation fields, and can be widely used in lightweight concrete, concrete blocks, sewage treatment and other fields.

[0076] It will be appreciated by those skilled in the art that the features described in the various embodiments of the present disclosure may be combined and / or combined in a variety of ways, even if such combinations or combinations are not explicitly described in the present disclosure. In particular, without departing from the spirit and teachings of the present disclosure, the features described in the various embodiments of the present disclosure may be combined and / or combined in a variety of ways. All of these combinations and / or combinations fall within the scope of the present disclosure.

[0077] The embodiments of the present disclosure are described above. However, these embodiments are only for illustrative purposes and are not intended to limit the scope of the present disclosure. Although the embodiments are described above, this does not mean that the measures in the various embodiments cannot be used in combination to advantage. Without departing from the scope of the present disclosure, those skilled in the art may make a variety of substitutions and modifications, which should all fall within the scope of the present disclosure.

Claims

1. A method for preparing acid-activated all-solid waste lightweight unburned ceramsite, characterized in that: include: S1: weigh the following raw materials in parts by weight: 21-35 parts of phosphogypsum, 12-18 parts of electrolytic manganese slag, 14-20 parts of dolomite, 15-32 parts of fly ash, 10-18 parts of blast furnace slag, 10-15 parts of high concentration phosphoric acid solution and 20-30 parts of water; S2: acid-leaching the phosphogypsum, and then mixing and grinding it with electrolytic manganese slag, dolomite, fly ash and blast furnace slag to obtain a mixed powder of unburned ceramsite raw materials; S3: moving the mixed powder of the unfired ceramsite raw materials to a granulator for stirring to obtain an unfired ceramsite mixture; S4: diluting the high-concentration phosphoric acid solution, and spraying the diluted phosphoric acid solution into a granulator at a uniform speed through a high-pressure spray pot to prepare spherical particles; S5: Move the spherical particles to a standard curing box for curing to obtain lightweight unfired ceramsite; Wherein, the pH value of the phosphogypsum described in step S1 is less than or equal to 4.5, and the fineness is greater than or equal to 0.25mm; the pH value of the electrolytic manganese slag described in step S1 is less than or equal to 5.5, and the content of calcium sulfate dihydrate is greater than or equal to 40%; the acid leaching treatment of the phosphogypsum described in step S2 includes: mixing oxalic acid and acetic acid solutions with a mass fraction of 1% each in a mass ratio of 1:2 to obtain an acidic solution, immersing the phosphogypsum in the acidic solution for immersion treatment, the immersion environment temperature is 25±2°C, the immersion time is 24 hours, and then drying in an oven at 50±5°C, and sealing for standby use.

2. The method for preparing acid-activated all-solid waste lightweight unburned ceramsite according to claim 1, characterized in that: The dolomite described in step S1 has a magnesium calcium carbonate content greater than or equal to 60%.

3. The method for preparing acid-activated all-solid waste lightweight unburned ceramsite according to claim 1, characterized in that: The fly ash described in step S1 is grade II fly ash.

4. The method for preparing acid-activated all-solid waste lightweight unburned ceramsite according to claim 1, characterized in that: The blast furnace slag described in step S1 is of grade S95.

5. The method for preparing acid-activated all-solid waste lightweight unburned ceramsite according to claim 1, characterized in that: The high concentration phosphoric acid solution described in step S1 has a concentration of 8-10 mol / L.

6. The method for preparing acid-activated all-solid waste lightweight unburned ceramsite according to claim 1, characterized in that: The stirring in step S3 is carried out at a speed of 65-75 r / min and lasts for 5-10 min.

7. The method for preparing acid-activated all-solid waste lightweight unburned ceramsite according to claim 1, characterized in that: The dilution of the high concentration phosphoric acid solution in step S4 is carried out according to the mass ratio of the high concentration phosphoric acid solution to water (1-1.5): (3-4).

8. The method for preparing acid-activated all-solid waste lightweight unburned ceramsite according to claim 1, characterized in that: The curing described in step S5 is to move the spherical particles into a standard curing box for curing for 28 days.

9. Acid-activated all-solid waste lightweight unburned ceramsite prepared by the method according to any one of claims 1 to 8.

10. Use of acid-activated all-solid waste lightweight unburned ceramsite prepared by the method of any one of claims 1 to 8 in the fields of water treatment, construction or transportation.

Citation Information

Patent Citations

  • A low-carbon, environmentally friendly, non-fired ceramsite filter media, its preparation method and applications

    CN114105536B

  • A variety of solid waste non-fired ceramsite based on phosphogypsum and its preparation method

    CN115368041B

  • Method for preparing building material from industrial solid waste

    CN113277819A

  • Phosphogypsum pretreatment liquid, preparation method thereof and application of phosphogypsum pretreatment liquid in oriented silicon steel coating

    CN118222126A

  • Unfired ceramsite and preparation method thereof

    CN118271059A